EFEKTIFITAS TERAPI AKUPUNKTUR, TUINA CHUZHEN MEDITATIF, KOMBINASI FOOD THERAPY TCM TERHADAP GANGGUAN SEMBELIT PADA MASA KEHAMILAN - Maris, Stella; Wardani, Frisca Desma Ayu Kusuma; Marjuki, Marjuki (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2022)
Background : The condition known as constipation occurs when the stools produced by the body's remaining nutritional metabolism become firm and difficult to defecate (Irianti, 2014). 17.4% of 575 Chinese women who sought medical care reported having acupuncture for reproductive issues. 19.5% of nurse midwives in North Carolina, according to another survey, utilized acupuncture during pregnancies (Allaire AD, 2000). For a number of illnesses, acupuncture treatment during pregnancy is showing promise.Objective: to determine whether the combination of acupuncture, tuina chuzhen, and TCM food therapy is effective against constipation disorders during pregnancMethod : The method used in the form of direct practice or demonstration to patients or subjects with a 26-year-old female patient Result : The patient said that after seven appointments over the course of more than a month, his bowel movements were regular and painless, and he could comfortably pass stools in 10 to 15 minutes on the toilet. Keywords : Constipation, pregnancy, akupuntur, tuina chuzhen, Traditional Chinese Medicine